Fleet-sizing for multi-depot and periodic vehicle routing problems using a modular heuristic algorithm - Rahimi-Vahed, Alireza; Gabriel Crainic, Teodor; Gendreau, Michel; Rei, Walter (Computers & operations research, 2015)
In this paper, we address the problem of determining the optimal fleet size for three vehicle routing problems, i.e., multi-depot VRP, periodic VRP and multi-depot periodic VRP. In each of these problems, we consider three kinds of constraints that are often found in reality, i.e., vehicle capacity, route duration and budget constraints. To tackle the problems, we propose a new Modular Heuristic Algorithm (MHA) whose exploration and exploitation strategies enable the algorithm to produce promising results. Extensive computational experiments show that MHA performs impressively well, in terms of solution quality and computational time, for the three problem classes.